Global patterns and substrate‐based mechanisms of the terrestrial nitrogen cycle. (2nd March 2016) - Niu, Shuli; Classen, Aimée T.; Dukes, Jeffrey S.; Kardol, Paul; Liu, Lingli; Luo, Yiqi; Rustad, Lindsey; Sun, Jian; Tang, Jianwu; Templer, Pamela H.; Thomas, R. Quinn; Tian, Dashuan; et al.
Abstract: Nitrogen (N) deposition is impacting the services that ecosystems provide to humanity. However, the mechanisms determining impacts on the N cycle are not fully understood. To explore the mechanistic underpinnings of N impacts on N cycle processes, we reviewed and synthesised recent progress in ecosystem N research through empirical studies, conceptual analysis and model simulations. Experimental and observational studies have revealed that the stimulation of plant N uptake and soil retention generally diminishes as N loading increases, while dissolved and gaseous losses of N occur at low N availability but increase exponentially and become the dominant fate of N at high loading rates. The original N saturation hypothesis emphasises sequential N saturation from plant uptake to soil retention before N losses occur. However, biogeochemical models that simulate simultaneous competition for soil N substrates by multiple processes match the observed patterns of N losses better than models based on sequential competition. To enable better prediction of terrestrial N cycle responses to N loading, we recommend that future research identifies the response functions of different N processes to substrate availability using manipulative experiments, and incorporates the measured N saturation response functions into conceptual, theoretical and quantitative analyses.